Enhanced immune responses to E2 protein and DNA formulated with ISA 61 VG administered as a DNA prime–protein boost regimen against bovine viral diarrhea virus. Issue 37 (5th September 2018) - Cai, Dongjie; Song, Quanjiang; Duan, Cong; Wang, Shenghua; Wang, Jiufeng; Zhu, Yaohong
Graphical abstract: Highlights: ISA 61 adjuvant-coated E2 protein and DNA vaccines against BVDV have been developed. E2 DNA priming–protein boosting improved antibody responses over solo vaccination. The DNA prime–protein boost strategy stimulated CD4 + and CD8 + T cell responses. The experimental vaccines elicited protection against BVDV in mice. Abstract: The aim of this study was to develop and test an optimal vaccination strategy against bovine viral diarrhea virus (BVDV) based on the E2 glycoprotein of the BJ1305 strain. To achieve higher E2-specific antibody titers and to broaden the cellular immune response, a plasmid encoding the E2 protein (pcDNA3.1-E2) was constructed and a purified recombinant E2 protein was generated. The E2 protein was emulsified in the adjuvant ISA 61 VG prior to administration. We immunized mice three times with pcDNA3.1-E2 or the recombinant E2 protein or primed twice with pcDNA3.1-E2 and boosted once with the E2 protein. To evaluate the protection against BVDV conferred by the vaccines, the mice were challenged with BVDV strain Oregon C24V after the third immunization. Although all immunized mice developed humoral and cellular immune responses, the E2-specific antibody titers in the DNA prime–protein boost group were significantly higher than those elicited by either the DNA or the protein vaccine. In addition, vaccination with the E2 DNA vaccine induced higher percentages of CD4 + IFN-γ + T cells and CD8 + IFN-γ + T cells among total CD3 + T cells than the other regimens. The predominant antibody subclass in the vaccinated mice was IgG1. Serum tumor necrosis factor alpha (TNF-α) levels in the DNA prime–protein boost group were significantly higher after the third immunization than in the other groups. Moreover, the mice treated with the DNA prime–protein boost vaccination regimen acquired protection against BVDV challenge, as shown by a significant reduction of viremia, only minor pathological changes, and a lower viral antigen burden than in the control and solo vaccinated mice. These results demonstrate the potential advantage of a DNA prime–protein boost vaccination approach over a solo vaccination for the prevention of BVDV. The ability of this vaccine strategy to control and eradicate BVD in herds warrants further investigation.